Development and Validation of a Novel Skills Training Model for PCNL, an ESUT project - Bozzini, Giorgio; Maltagliati, Matteo; Berti, Lorenzo; Vismara, Riccardo; Sanguedolce, Francesco; Crisci, Alfonso; Fiore, Gianfranco Beniamino; Redaelli, Alberto; Pastore, Antonio Luigi; Gozen, Ali; Breda, Alberto; Scoffone, Cesare; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The aim of this study is to validate a totally non biologic training model that combines the use of ultrasound and X ray to train Urologists and Residents in Urology in PerCutaneous NephroLithotripsy (PCNL). Methods: The training pathway was divided into three modules: Module 1, related to the acquisition of basic UltraSound (US) skill on the kidney; Module 2, consisting of correct Nephrostomy placement; and Module 3, in which a complete PCNL was performed on the model. Trainees practiced on the model first on Module 1, than in 2 and in 3. The pathway was repeated at least three times. Afterward, they rated the performance of the model and the improvement gained using a global rating score questionnaire. Results: A total of 150 Urologists took part in this study. Questionnaire outcomes on this training model showed a mean 4.21 (range 1-5) of positive outcome overall. Individual constructive validity showed statistical significance between the first and the last time that trainees practiced on the PCNL model among the three different modules. Statistical significance was also found between residents, fellows and experts scores. Trainees increased their skills during the training modules. Conclusion: This PCNL training model allows for the acquisition of technical knowledge and skills as US basic skill, Nephrostomy placement and entire PCNL procedure. Its structured use could allow a better and safer training pathway to increase the skill in performing a PCNL.